Pengaruh Law and Order Situation Terhadap Foreign Direct Investment (FDI) di Indonesia - Faradila, Mutia (Media Hukum Indonesia (MHI), 2025)
In this research the author will discuss about the influence of one of the risks that is The law and order situation on investment protection in Indonesia. The authors in this study used a normative legal research method, i.e. research focused on the study of prevailing positive legal norms as well as relevant legal doctrines.Overall, foreign capital investment or FDI has a major role in boosting Indonesia’s economic growth through job creation, skill improvement and employment generation. Additionally the injection of foreign capital or Foreign Direct Investment (FDI) is highly affected by the legal, political, and security conditions of a country. Foreign investors will invest their capital only if they feel safe and confident that the destination country has strong law enforcement as well as a stable law and order situation. However, in Indonesia, various issues such as overlapping land permits, agrarian conflicts, weak protection of indigenous peoples’ rights, to the emergence of armed conflicts such as the activities of Armed Criminal Groups (ACC) in Papua, pose serious challenges for investment stability. Inconsistent law and order conditions often give rise to legal uncertainty and reduce the interest of foreign investors to invest.